DETERMINATION OF CALCIUM (Ca) AND MAGNESIUM (Mg) CONTENT IN CACAO (Theobroma cacao Linn) FERMENTATION AND NON FERMENTATION BY SPECTROPHOTOMETRY - -, Wiranda; Syukur, Sumaryati; Aziz, Hermansyah (Jurnal Riset Kimia, 2009)
ABSTRACT Cacao beans contain many kinds of mineral, magnesium (Mg), calcium (Ca), Zinc (Zn), Phosphor (P) and etc. This study investigated magnesium (Mg) and calcium (Ca) in fermentation and non fermentation cacao beans by atomic absorption spectrophotometry. Mg and Ca, content in non fermentation cacao beans of green and red variety are 453 µg/g, 466 µg/g, and 491 µg/g, 445 µg/g. Mg and Ca, contents  in fermentation cacao beans of green and red variety are, 596 µg/g, 528 µg/g, and 554 µg/g, 505 µg/g. Fermentation make magnesium (Mg) and calcium (Ca) content increase significantly. Keywords : Theobroma cacao Linn, fermentation, spectrophotometry.